The Effect of Abdominal Binders on Mobilization and Pain in the Postoperative Period after Emergency Laparotomy - Anis Ahmed, Malik Irfan Ahmed, Yasmeen Iqbal, Ali Kamran, Mahnoor Ahmed, Asma Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In order to augment the postoperative recovery process in patients undergoing laparotomy, various methods have been evaluated in the past. One such strategy is the use of postoperative abdominal binder. Objective: We compared the efficacy of abdominal binder use in patients undergoing emergency laparotomy by objective comparison of 6-minute walk test and pain on visual analogue scale. Place of study: Departments of Surgery in both Benazir Bhutto Hospital and District Head Quarter Hospital affiliated with Rawalpindi Medical University, Rawalpindi Material and Methods: It was a randomized controlled trial that was carried out at Departments of Surgery of Rawalpindi Medical University, from October 2021 till May 2022. It included 100 patients, 50 in binder group and 50 in non-binder group. The study included patients from 18 to 65 years of age undergoing emergency exploratory laparotomy for acute abdomen or abdominal trauma having ASA Class I-II. In the postoperative period mobility was assessed by 6-minute walk test (6MWT) and pain was assessed using the VAS. Data was analyzed using SPSS version 20. The mean 6 MWT distance and pain score (VAS) was compared between the binder and no-binder group using the independent samples t-test. Results were considered statistically significant if the p value was < 0.05. Results: The 6MWT distance and the pain scores of patients in the binder group did not differ significantly from the pain scores in the non-binder group on first, third, fifth and fourteenth postoperative day (p>0.05). Conclusion: We did not find a statistically significant difference between the patients using binder and the patients not using binder after surgery with respect to mobilization and pain in the postoperative period. Keywords: major abdominal surgery; exploratory laparotomy, abdominal binder; 6-minute walk test; visual analogue scale